Fabrication of optical Raman spectrometer - Chua, Audrey An Qi (2017)
Dispersive Raman spectroscopy is a non-invasive imaging methodology which can be used in detection of various specimens. The intention of this project is to demonstrate the possible usage and the effectiveness of the fabricated spectrometer. The fabricated spectrometer allows for the projection of a coherent light source on a biological specimen to produce characteristic peaks to be formed. Identification of the characteristic peaks can be used to determine the biological nature and content of the specimen itself. To achieve possible Raman scatterings, the precision, arrangement and selection of components are modified to capture an image of high resolution .